Implementation of Green Human Resource Management Towards Green Employee Behavior Mediated by Top Management Commitment in Higher Education - Albert Kurniawan Purnomo; Yoana Nurul Asri; Theresia Marditama (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study explores the rising importance of Green Employee Behavior (GEB) within organizations, particularly in higher education institutions, as environmental concerns continue to escalate. Companies are increasingly adopting Green Human Resource Management (GHRM) to align employee behaviors with environmental sustainability goals, which enhances the company’s reputation. However, research on GEB in higher education remains limited. Using a quantitative research method and data analysis through Structural Equation Modeling (SEM) with SmartPLS software, this study gathered primary data through questionnaires distributed to universities, such as Nurtanio University Bandung, Jenderal Achmad Yani University, and Maranatha Christian University, with a focus on lecturers holding structural roles. The sample included 51 respondents, obtained via convenience sampling, with data collected through Google Forms shared on WhatsApp groups and personal chats. The study examined the direct impact of GHRM on GEB and explored the mediating role of Top Management Commitment. The results revealed that GHRM has a significant direct influence on GEB within higher education institutions. However, Top Management Commitment was not found to have a direct influence on GEB nor did it mediate the relationship between GHRM and GEB. This study contributes to raising awareness among academics about the importance of practicing GEB and addresses the gap in research on environmental sustainability practices in higher education.